LEADERSHIP AND INCENTIVE AFFECTION DUE TO THE WORKING SPIRIT OF EMPLOYEES AT PT. BANK CENTRAL ASIA (BCA) FINANCE BRANCH-PEKANBARU - Eka Trina Safitri; Dewita Suryati Ningsih; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Bank Central Asia (BCA) Finance Branch Pekanbaru in order to know how leadership and incentive can affect simultaneous and partially to employee’s working spirit at PT. Bank Central Asia (BCA) Finance branch Pekanbaru and also to find out how leadership can indirectly influence employee’s working spirit through incentive given at PT. Bank Central Asia (BCA) Finance Branch Pekanbaru. The population in this study were all the employees at PT. Bank Central Asia (BCA) Finance Branch Pekanbaru, with 46 respondents for the sample. The sampling method used is census and the testing method of data quality using validity and reliability test, the classical assumption test, the MSI method, and the method of path analysis using SPSS version 20. The final test results, stating that the former leadership and incentive contribute simultaneously and significantly to the working spirit of employee. Leadership and incentive affect partially on employee’s working spirit. Leadership affect indirectly in employee’s working spirit through incentive. From this research, we can see that employee’s spirit as variables must be improved to give satisfaction for the employees. When talking about leadership as variables, leader must pay more attention for the employees, and the last, in incentive variables, giving incentive would be better if depends on working quality and quantity of the employees.Keywords: Working Spirit, Leadership, Incentive